2003
DOI: 10.1590/s0100-879x2003000600011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber, energy intake and nutritional status during the treatment of children with chronic constipation

Abstract: The present prospective study was carried out to determine dietary fiber and energy intake and nutritional status of children during the treatment of chronic constipation. Twenty-five patients aged 2 to 12 years with chronic constipation were submitted to clinical evaluation, assessment of dietary patterns, and anthropometry before and after 45 and 90 days of treatment. The treatment of chronic constipation included rectal disimpaction, ingestion of mineral oil and diet therapy. The standardized diet prescribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 14 publications
1
23
0
10
Order By: Relevance
“…Özellikle kuru erik, armut ve elma suyunda bulunan sorbitol en çok önerilen karbohidrat tipidir (24,25) . Diyet ile alınan liflerin çocuklardaki kabızlık üzerine etkileri tartışmalıdır (26)(27)(28)(29) . Çocukların kabızlık tedavisine destek olarak tam tahıl, meyve ve sebze içeren dengeli bir diyet önerilmektedir (12) .…”
Section: Fonksiyonel Kabızlık Tedavisiunclassified
“…Özellikle kuru erik, armut ve elma suyunda bulunan sorbitol en çok önerilen karbohidrat tipidir (24,25) . Diyet ile alınan liflerin çocuklardaki kabızlık üzerine etkileri tartışmalıdır (26)(27)(28)(29) . Çocukların kabızlık tedavisine destek olarak tam tahıl, meyve ve sebze içeren dengeli bir diyet önerilmektedir (12) .…”
Section: Fonksiyonel Kabızlık Tedavisiunclassified
“…Agradeço terem chamado a atenção e cito, nas referências da presente carta, além da referida meta-análise, de 1988 6 , estudo controlado duplo-cego subseqüente 7 . Tais estudos demonstraram o efeito benéfico do farelo de trigo em adultos constipados, como dito no editorial 2 .…”
Section: Mauro Batista Moraisunclassified
“…Esses comentários não devem ser interpretados como um endosso para o uso de fibras solúveis no tratamento da constipação. Aliás, em nossa primeira tentativa sistematizada de terapia nutricional da constipação em crianças, recomendamos o emprego de dieta com aumento da quantidade de alimentos ricos em fibra alimentar, que normalmente fazem parte do hábito alimentar da população e que contêm tanto fibra alimentar solúvel como insolúvel 7 .…”
unclassified
“…A study of the treatment of children with chronic functional constipation found that the median increase in dietary fiber consumption, when the source is items from the habitual diet, while statistically significant, did not reach the minimum recommended in published literature, despite good clinical progress, in a scenario of a treatment program including disimpaction, educational measures and mineral oil in addition to dietary intervention. 10 We performed, at our unit, a randomized, doubleblind clinical trial to evaluate the efficacy of a soy polysaccharide fiber supplement for the treatment of chronic functional constipation in children, using a soy formula with no fiber as placebo. Because the preliminary results of that study did not confirm the expected efficacy of polysaccharide fiber for chronic constipation treatment, 11 the current experimental project was designed in order to compare, in rats, the effects of soy polysaccharide on fecal weight and humidity and compare them with the effects of cellulose and a soy formula with no dietary fiber.…”
Section: Introductionmentioning
confidence: 99%